Environmental awareness--air pollution - Snodgrass, Mary Ellen; Oelerich, Marjorie L.; Vista III Design (Marco, Fla. : Bancroft-Sage Pub., 1991)
Discusses the different types of air pollution and how they can be stopped or reduced.
Includes index.
Booklist.
School Library Journal.
6.5.
6.5
3-6
Keywords: Air quality management -- Juvenile literature; Air -- Pollution -- Juvenile literature; Air -- Pollution; Pollution; Air pollution; Pollution